Keefektifan Virtual Class dengan Google Classroom dalam Pembelajaran Fisika Dimasa Pandemi Covid-19 - Permata, Andira; Bhakti, Yoga Budi (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2020)
At this time, the school is conducting online learning from home due to the Covid-19 pandemic, but teachers and students still do online-based or Virtual Class learning through various applications, one of which is Google Classroom. The implementation of Google Classroom is still very public for learners, because usually teachers teach face-to-face. The purpose of this article is to determine the effectiveness of the Virtual Class implementation with Google Classroom in the Covid-19 pandemic Physics study. The method used in the form of charging poll through the Google Form in junior high school class VII-IX randomly represents one province namely West Java. From the results of a descriptive survey the results of the Google Classroom are less effective in physical learning, but are effective in virtual class learning and can be used as a Covid-19 pandemic learning app. So it can be concluded that students still need teachers directly in the process of learning physics.